A qualitative assessment of insomnia in recovering alcohol‐dependent patients - Olena Zhabenko; Igor V. Linskiy; Oleksandr I. Minko; Valeriy N. Kuzminov; Meike Gmeinwieser; Lars P. Kiefer; Deirdre A. Conroy (Wiley, 2023)
Abstract Insomnia is a common symptom that may interfere with the efforts of alcohol‐dependent patients to initiate and maintain sobriety. This study investigates the experiences of recovering alcohol‐dependent patients with insomnia as well as preferences for treatment strategies. Semi‐structured interviews were conducted with 27 patients in Ukraine and Germany. Most of the patients experienced negative psychological (n = 21), physiological (n = 14) effects and negative daytime consequences during insomnia. All 27 patients were engaged in nonpharmacological approaches to insomnia and 52% used pharmacological approaches to manage insomnia. This study provides insight for understanding how alcohol‐dependent patients in recovery perceive insomnia.